OPTICAL PROPERTIES OF LASER-COLOURING MARKED STAINLESS STEEL (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
Laser colour-marking method often displace conventional marking techniques. Complicated technology of laser-induced periodic surface structure creation on stainless steel samples allows changing their surface morphology and optical properties, which were studied in this work by atomic force microscopy (AFM), laser scanning microscopy, reflectance spectroscopy and ellipsometry. Reflectance spectra of the samples demonstrate reflectance maxima correlate with the visible colours of the samples and with the extrema in the non-monotonic spectral dependences of the derivative of real part of complex dielectric permittivity extracted from the ellipsometric data. Thus, the most intensive light scattering takes place when the real part of complex dielectric permittivity falls down quickly with changing wavelength. We did not observe any “azimuth anisotropy” in our optical measurements at constant incidence angle: the spectra were the same independently of the light incidence plane orientation (parallel or perpendicular to the previous laser light spot scanning direction). We suppose that this selective resonance-like light scattering is due to the sample surface inhomogeneity, which is the result of previous laser treatment. This assumption agrees with estimations based on laser microscope and AFM images as well as with predictions of Mie theory. Thus, the colours of the samples under study are due to the light scattering by randomly distributed surface species with different sizes.